2017
DOI: 10.3899/jrheum.161109
|View full text |Cite
|
Sign up to set email alerts
|

The OMERACT Core Domain Set for Outcome Measures for Clinical Trials in Polymyalgia Rheumatica

Abstract: This core domain set was considered sufficiently well-defined that the next step will be to apply the OMERACT Filter 2.0 Instrument Selection Algorithm to select candidate instruments for a subsequent "deeper dive" into the data. This will allow instruments to be mapped onto each of our core domains to derive a core outcome set for PMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Thresholds to define relapse have been proposed 43 , but these measures are not widely used in clinical practice and trials. An OMERACT study group for PMR identified systemic inflammation (detected via laboratory markers), physical function, pain and stiffness as core outcomes that should be evaluated in all clinical trials and should be incorporated into a new score for assessing PMR disease activity 44 .…”
Section: Clinical Monitoringmentioning
confidence: 99%
“…Thresholds to define relapse have been proposed 43 , but these measures are not widely used in clinical practice and trials. An OMERACT study group for PMR identified systemic inflammation (detected via laboratory markers), physical function, pain and stiffness as core outcomes that should be evaluated in all clinical trials and should be incorporated into a new score for assessing PMR disease activity 44 .…”
Section: Clinical Monitoringmentioning
confidence: 99%
“…Besides, higher percentage of patients relapsed during the reduction of glucocorticoid among those with PMR, while more patients had infections due to immune suppression treatment among those without PMR. Therefore, it is necessary to highlight the importance of follow-up and integrated management of GCA patients, and the reasons for poor prognosis in some GCA patients should be examined [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Since the Outcome Measures in Rheumatology (OMERACT) Filer 2.0 resulted in successful development and implementation of COSs for many other diseases, we used their methodology [16][17][18][19][20][21][22]. The OMERACT Filter is a conceptual framework which encompasses the entire content of what is measureable in a study.…”
Section: Methodsmentioning
confidence: 99%